Automated Assessment, Face to Face - Al-Sayyed, Rizik M. H.; Hudaib, Amjad; AL-Shboul, Muhannad; Majdalawi, Yousef; Bataineh, Mohammed (International Journal of Emerging Technologies in Learning (iJET), 2010)
This research paper evaluates the usability of automated exams and compares them with the paper-and-pencil traditional ones. It presents the results of a detailed study conducted at The University of Jordan (UoJ) that comprised students from 15 faculties. A set of 613 students were asked about their opinions concerning automated exams; and their opinions were deeply analyzed. The results indicate that most students reported that they are satisfied with using automated exams but they have suggestions to improve the automated exam deployment.